Generalized epilepsy and myoclonic seizures in 22q11.2 deletion syndrome - Strehlow, Vincent; Syrbe, Steffen (Molecular syndromology, 2016)
Prompted by the observations of juvenile myoclonic epilepsy (JME) in 22q11.2 deletion syndrome (22q11DS) and recurrent copy number variants in genetic generalized epilepsy (GGE), we searched for further evidence supporting a possible correlation of 22q11DS with GGE and with myoclonic seizures. Through routine diagnostics, we identified 3 novel individuals with the seemingly uncommon combination of 22q11DS and JME. We subsequently screened the literature for reports focussing on the epilepsy phenotype in 22q11DS. We additionally screened a database of 173 22q11DS patients and identified a fourth individual with JME as well as 2 additional cases with GGE. We describe 6 novel and 22 published cases with co-occurrence of 22q11DS and GGE. In many patients, GGE was associated with myoclonic seizures allowing for a diagnosis of JME in at least 6 individuals. Seventeen of the 173 22q11DS cases (10%) had a diagnosis of either focal or generalized epilepsy. In these cases, focal epilepsy could often be attributed to syndrome-associated hypocalcaemia, cerebral bleeds, or structural brain anomalies. However, the cause of GGE remained unclear. In this study, we describe and review 28 individuals with 22q11DS and GGE (especially JME), showing that both disorders frequently co-occur. Compared to the reported prevalence of 15-21%, in our case series only 10% of 22q11DS individuals were found to have epilepsy, often GGE. Since 22q11.2 does not contain convincing GGE candidate genes, we discuss the possibility of an aetiological correlation through a possibly disturbed interaction with the GABAB receptor.